2016
DOI: 10.1111/jhn.12437
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐6 polyunsaturated fatty acids, serum zinc, delta‐5‐ and delta‐6‐desaturase activities and incident metabolic syndrome

Abstract: Higher serum total n-6 PUFA, linoleic acid and arachidonic acid concentrations and D5D activity were associated with a lower risk of developing metabolic syndrome and higher D6D activity was associated with a higher risk. The role of zinc also needs to be investigated in other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…One of the studies found an inverse association between serum total n-6 PUFAs and incident MetS among 665 Finnish men and women (10). Similar associations were also observed in another study that consisted of 661 middle-aged Finnish men (29). In addition, increased circulating levels of total n-6 PUFAs were associated with decreased incidence of type 2 diabetes or CHD in several European studies (30,31).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…One of the studies found an inverse association between serum total n-6 PUFAs and incident MetS among 665 Finnish men and women (10). Similar associations were also observed in another study that consisted of 661 middle-aged Finnish men (29). In addition, increased circulating levels of total n-6 PUFAs were associated with decreased incidence of type 2 diabetes or CHD in several European studies (30,31).…”
Section: Discussionsupporting
confidence: 57%
“…Notably, existing results regarding the associations of specific n-6 PUFAs with cardiometabolic diseases remain controversial among individual studies. For instance, Yary et al (29) found that both serum 18:2n-6 and 20:4n-6 were inversely associated with future MetS risk in Finnish men.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma phospholipid levels of C20:3n-6 were also positively associated with BMI in participants from the USA and Mexico. 13,17 There was, however, also a longitudinal study that found higher total circulating n-6 PUFAs, in particular linoleic acid and arachidonic acid, to be protective of risk factors for the MetS, including both systolic and diastolic BP and plasma triglycerides in men, 24 indicating that different n-6 FAs showed opposite associations with the MetS. The association of C20:3n-6 with the MetS requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…17 Some studies also report positive associations of specific plasma phospholipids n-6 PUFAs with metabolic risk, 18,22 while other studies report inverse associations of total n-6 PUFAs in erythrocytes and serum, respectively, with the MetS. 23,24 Due to inconsistent results in different studies relating to circulating n-6 PUFAs, further research to understand their role in association with obesity and the MetS is highly recommended. 25 Since people consume food rather than individual nutrients, it is difficult to isolate the individual nutrients in the diet and link them to disease and health.…”
mentioning
confidence: 99%
“…Large scale studies in human populations, however, are challenging this argument and demonstrating potential beneficial roles of omega-6 fatty acids, including arachidonic acid, which has both pro-inflammatory and antiinflammatory properties [28]. A prospective study with 661 older men followed over ten years showed that higher serum omega-6 fatty acids, including arachidonic acid, resulted in a lower risk of developing metabolic syndrome [29]. Pooled analysis from 39,740 adults in 20 prospective cohort studies assessed the role of omega-6 fatty acids in the development of type 2 diabetes and concluded that arachidonic acid was not harmful [30].…”
Section: Plos Onementioning
confidence: 99%